A Critical Appraisal on Amending Contemporary Laws With A View to Enhance Women's Participation in the Sri Lankan Labour Force - Methma, R. (The Department of Law, Faculty of Arts, University of Jaffna / Surana and surana International Attorneys India, 2025)
Women play a significant role in the society. Women's rights refer to the legal, social, and cultural entitlements that promote fair, equality and justice for women for every aspect of their lives. Women were marginalized due to many social cultural and norms in the history. However there have been developments in the laws in order to protect the rights of women in both national and d international level. Similarly, the labour force of a country plays a key role in shaping its economy. In a country the labour force consisting of both men and women, it can be classified as public and private sector. The respective workforce contains individuals who are employed, unemployed or actively seeking employment. Irrespective of the educational attainment, it is identified that there is low female labour force participation has been oscillating throughout the years. It is identified that female unemployment rates recorded a higher number than male unemployment comparatively. This research aims at reviewing whether the prevailing legal system in Sri Lanka establishes women’s right to employment and in Women’s rights in employment when participating in workforce and whether the law adequately protect the rights of the women when participating in the work force compared to international standards. Therefore, the main objective of the research is to examine whether the right to employment of the female workforce in Sri Lanka is adhering into the standards of International Labour law framework specifically based on the ILO standards applicable to Sri Lanka. A library-based data collecting method is used in order to achieve the said objective of this project. The relevant primary and secondary sources are used to comparatively analyse the applicable Sri Lankan and International standards. In the History of Sri Lanka many factors can be identified as the factors effecting the women workforce participation. However, while perusing through the relevant legislative enactments, it can be recognized that there are ‘protective’ approaches that have been taken.
Keywords: Women’s rights; Right to employment; ILO standards